Impact of breast cancer awareness program on breast screening utilization among women in the United Arab Emirates: A cross-sectional study - Raseena Aboobacker Abdulla; Nafeesa Abdul Kareem; Rifah Anwar Assadi; Afreen Abdul Rahim Sanaullah; Sathyapriya Nandagopal; Shahnaz Mohamed Wazil; Jayakumary Muttappallymyalil (BMC Public Health, 2025)
Abstract Background Breast cancer is the most common type of cancer and the leading cause of cancer death among women worldwide. In 2020, approximately 2.3 million women were newly diagnosed with breast cancer, resulting in around 685,000 deaths globally. The high incidence and prevalence of breast cancer have made it a major public health problem in both developed and developing nations, leading to overburdened health systems and increased direct medical expenditure. This research was conducted to assess the impact of breast cancer awareness programs on breast screening utilization among women in the United Arab Emirates. Methods A cross-sectional study using a content-validated interviewer-administered questionnaire was conducted among 959 women aged ≥ 20 years from 31st May 2023 to 31st October 2024, in the United Arab Emirates. Data on sociodemographics, awareness program participation, screening utilization, and barriers were analyzed using descriptive statistics and chi-square tests. Results Among the study participants,304 (31.7%) had attended awareness programs. Attendance was associated with younger age, higher education, and being single (p < 0.001). Among those who have ever attended any breast cancer awareness programs who had utilized the screening were 38.5% compared to 13.3% non-attendees (p < 0.001). The study concluded that age, education level, and marital status were significantly associated with participation in breast cancer awareness programs (p-value < 0.05). Key barriers included a lack of physician recommendations (24.3%), knowledge gaps (23%), and cost concerns (22.6%). Conclusions The study shows that participation in the awareness programs varied based on age, education and marital status, additionally, those with lower educational levels had a higher attendance at the awareness programs, emphasizing the significance of educational initiatives. The study showed a link between attending breast cancer awareness programs and the use of screening services, furthermore, notable gap in screening utilization such as emotional and perceived barriers were noted. Thus, its necessary to overcome these challenges for enchaning early detection and treatment outcomes. Interventions such as targeted educational campaigns, improved screening facility and better communication between physicians and patients can aid in addressing these challenges.